Analysis of average daily and lactation milk yield using Rank Correlation study - Kumar, Vijay; CHAKRAVARTY, A K; PATIL, C S; MAGOTRA, ANKIT; SHIVAHRE, P R (Indian Journal of Dairy Science, 2018)
The data pertaining to first lactation 305-days or less milk yield (FL305MY) and first lactation average daily milk yield (MY/FLL) of Murrah buffalo during 1993 to 2010 at National Dairy Research Institute, Karnal; Central Institute for Research on Buffalo, Hisar; Guru Angad Dev Veterinary and Animal Sciences University, Ludhiana and Choudhary Charan Singh Haryana Agricultural University. The aim of the study was to investigate efficiency of sire evaluation based on MY/FLL compared to FL305MY using contemporary comparison method and simple regressed least-squares method for genetic evaluation of Murrah buffalo bulls. The rank correlations between corresponding ranks based on MY/FLL and FL305MY ranged from 0.745 to 0.950 using Contemporary comparison method. The rank correlations between corresponding ranks based on MY/FLL and FL305MY ranged from 0.818 to 0.991 using simple regressed least-squares method. Â It was found that rank correlations between two traits for sire evaluation were highly statistically significant indicating that both traits of sire evaluation were equally effective to discriminate amongst sires.